Induction of Apoptosis and Inhibition of Growth of Human Hepatoma HepG2 Cells by Heparin - (:unkn) unknown (My University, 2003)
Background/Aims: Apoptotic and anti-proliferative effects of heparin on a number of cancers have been described. There have been no studies analyzing the effect of heparin on human hepatoma cells. The aim of this study was to investigate the effect of heparin on human hepatoma cell line, HepG2. Methodology: HepG2 cell line was cultured with different concentrations of heparin. Colony count, viability assay, percentage of the apoptosis and proliferative index were assessed at the end of the 7th day. Trypan blue was used to assess viability. Apoptosis and proliferative indexes were assessed by flow-cytometry. Results: Hepatoma cells were arrested at the G 0/G 1 phase with heparin incubation and proliferative indexes decreased significantly in 20, 40 and 80 U/mL of heparin concentrations in comparison with the control (36±1%, 30±5% and 29±8% vs. 44±1%, p<0.01). Flow cytometry revealed a statistically significant increase in apoptosis in groups incubated with 40 and 80 U/mL of heparin in comparison with the control (39±26% and 58±18% vs. 0.83±1.3%, p<0.01). Colony counts per well and viable cells per μL decreased significantly in 80 U/mL of heparin. Conclusions: Heparin leads to a significant anti-proliferative and an apoptotic effect on human hepatoma cells in vitro.
Keywords: Apoptosis; Heparin; Hepatoma; Proliferation